Coupling Coordination between Innovation Capability and Financial Competitiveness in China’s Energy Enterprises under the Belt and Road Initiative - Chen, Anxin; Yan, Ruikun (European Scientific Journal, ESJ, 2026)
The Belt and Road Initiative has accelerated the overseas expansion of Chinese energy enterprises, yet the synergy between their technological innovation and financial competitiveness remains under-explored. This study examines the coupling mechanism between innovation capability( defined as a comprehensive embodiment of the dual dimensions of innovation resource input and innovation outcome output) and financial core competitiveness (defined as a composite of operational efficiency, profitability, and growth potential) of these firms. Using entropy-weighted TOPSIS, coupling coordination, and grey relational models, we analyse panel data from eight major energy enterprises from 2018 to 2024. The results show a stark asymmetry: innovation capability increased steadily, while financial competitiveness fluctuated sharply, plummeting to 0.103 in 2020 before rebounding to 0.270 in 2024. As a result, the coupling coordination degree evolved from a mild imbalance through antagonistic growth to short-term adjustment, indicating a fragile yet progressive synergy. This study concludes that enhancing the precision of technology investment and cross-border financial coordination are key to strengthening the innovation-finance nexus, offering quantitative insights for the sustainable growth of energy enterprises in complex international contexts.